Family-based care model for dependent elderly: Integration family systems nursing theory and disengagement theory to achieve sustainable development goals - Mendrofa, Fery Agusman Motuho (Edelweiss Applied Science and Technology, 2025)
The aim of this research is to design an innovative family-centered care model using Family Systems Nursing Theory and Disengagement Theory in an effort to address the needs of dependent elderly individuals and support the 2030 SDG agenda. A sequential mixed-methods design collected data from 120 families with dependent elderly individuals, 45 healthcare providers, and 25 community stakeholders through surveys, interviews, focus groups, record reviews, and direct observation. Formal support systems had significant gaps, with 78% of care work falling onto untrained family members. The proposed model establishes a multi-level intervention system aimed at family empowerment, balanced disengagement, and community integration in alignment with SDGs 3 and 10 through three interlocking care circles. The model was found to demonstrate enhanced quality of life for both elderly individuals and caregivers considerably while reducing the need for hospitalization to a large degree. The approach enables sustainable elderly care by providing a culturally sensitive response to aging problems. The model positions healthcare professionals as facilitators instead of principal providers, empowering families through knowledge and skill enhancement while activating extended family members, volunteers, and formal services.